2012
DOI: 10.1080/13523260.2012.693792
|View full text |Cite
|
Sign up to set email alerts
|

Bandwagoning, Not Balancing: Why Europe Confounds Realism

Abstract: Although realist perspectives seem challenged to explain European choices and preferences, realism retains great utility with its stress on states and states' concern for their national interests. Traditional realist analysis of European security policy err, rather, by focusing on balancing and related concepts such as soft balancing and balancing for autonomy. These accounts are theoretically and empirically flawed. Whilst balancing perspectives shed some light on European security policy predispositions, ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 30 publications
(40 reference statements)
0
6
0
1
Order By: Relevance
“…Disaggregation helps measure the extent to which a country is actually pursuing shared objectives. It helps distinguish between bandwagoning (Sweeney & Fritz, 2004;Cladi & Locatelli, 2012) and balancing -hard (Posen, 2006) or soft (Pape, 2005). Disaggregating avoids conflating spending on collective defense and 0 2,000 4,000 6,000 8,000 10,000 Figure 5 demonstrates the significant variation in the composition of 2014 defense budgets across the transatlantic community.…”
mentioning
confidence: 99%
“…Disaggregation helps measure the extent to which a country is actually pursuing shared objectives. It helps distinguish between bandwagoning (Sweeney & Fritz, 2004;Cladi & Locatelli, 2012) and balancing -hard (Posen, 2006) or soft (Pape, 2005). Disaggregating avoids conflating spending on collective defense and 0 2,000 4,000 6,000 8,000 10,000 Figure 5 demonstrates the significant variation in the composition of 2014 defense budgets across the transatlantic community.…”
mentioning
confidence: 99%
“…5 However, although they refer frequently to sentiments such as intentions, preferences, concerns, or motives, these are sentiments that are taken as given and as relatively unproblematic. Indeed, the nature of agency remains troublingly underspecified as the question of how agents arrived at their particular sentiment is completely ignored.…”
Section: The Overlooked Importance Of Intentionsmentioning
confidence: 99%
“…18 Supranational studies assert that EU institutions spearhead defence integration, while proponents of the intergovernmental perspective credit the expanding role of collective decision-making in defence policy to the initiative and stewardship of member state (hence, "new" intergovernmentalism). 19 Based on new intergovernmentalism, 20 it has been generally confirmed that security and defence policy advancements, including in the context of Russia's war, testify to the fact that "intergovernmental consensus and deliberation [have] effectively sidelined supranational institutions." 21 Furthermore, issues pertaining to defence policy strategy and defence industrial interests have taken on a more prominent role in deliberations among member states, 22 thus indicating a relatively greater degree of cooperation at the political level.…”
Section: Perspectivementioning
confidence: 99%